Thanks a lot, COVID : holistic thinking, gratitude and positive reframing amidst the COVID-19 pandemic - Lee, Liang Ying (Nanyang Technological University, 2021)
The present research examined the role of holistic thinking and gratitude in positively reframing the pandemic. From past work, we know that holistic thought and the practice of gratitude buffers against the negative psychological impacts of stressors. However, direct links between holistic thinking, gratitude, and positive reframing have yet to be made. Three studies were conducted to examine these relationships. The pilot study investigated the COVID-19 related stressful events experienced by Americans in their day to day lives. Thematic analyses revealed 12 categories of stressful events, including mask-wearing, constant cleaning, and working from home. Study 1 involved using correlational and mediational analyses to investigate the relationship between holistic thinking, gratitude, and positive reframing. The results showed that holistic thinking, gratitude, and positive reframing were positively and significantly correlated, and that gratitude partially explained the link between holistic thinking and positive reframing. Study 2 was a high-powered, pre-registered replication of Study 1, which included meaning making as an exploratory variable. The core findings of Study 1 were replicated. Exploratory analyses revealed that holistic thinking, gratitude, meaning making, and positive reframing were positively correlated, and meaning making partially explained the link between holistic thinking and positive reframing. All of the above findings could not be explained by alternative accounts, such as age, gender, perception of COVID-19 related stressful events (as identified in the pilot study), and COVID-19 related threat. We discuss the implications of holistic thinking, gratitude, and meaning making in the context of COVID-19, and how it could help people positively reframe the pandemic.